The biochemical basis of neuropharmacology - Cooper, Jack R.; Bloom, Floyd E.; Roth, Robert H. (USA : Oxford University Press, 1982)
Fluorescence photomicrograph of rat locus ceruleus. Norepinephrine-containing neurons and their processes fluoresce a bright green-blue owing to condensation with glyoxylic acid. Blood vessels perfused with pontamine sky-blue fluoresce red.
Keywords: Pharmacology; Neuropharmacology; Neuropharmacology